Contemporary Strategies in the Management of Civilian Neck Zone II Vascular Trauma - Karaolanis, Georgios; Maltezos, Konstantinos; Bakoyiannis, Chris; Georgopoulos, Sotiris (Frontiers in Surgery, 2017)
Neck trauma is the leading cause of death mainly in younger persons that sets some surgeons faced with the difficult and controversial decision whether to repair or ligate vascular injuries in the presence of coma and /or central neurological deficit. Vascular injuries in zone II predominate over the other injuries located in zones I /III of the neck. Traditional open repair of carotid injuries with primary closure or interposition grafting is always recommended due to the effective long-term results for penetrating injuries or for patients unfit for endovascular intervention. In cases of blunt trauma anticoagulation or anti-platelet therapy should be administered firstly in neurologically stable patients. In case of worsening of the neurological status of the patient despite adequate anti-coagulation or contraindication for anti-thrombotic therapy, endovascular means should be attempted in arterial lesions suitable for endovascular repair. We provide an update on penetrating/blunt trauma in zone II of the neck, giving emphasis on the anticoagulant and endovascular treatment.